A new role for fluorine-18-fluorodeoxyglucose positron-emission tomography/computed tomography in Erdheim-Chester disease - Ciska-Anne Van Keerberghen; Antoine Harrouk; Luca Leone (World Journal of Nuclear Medicine)
Erdheim-Chester disease (ECD) is a rare form of non-Langerhans cell histiocytosis, with multisystem manifestation such as bone pain, being the most common presenting symptom, cardiovascular or central nervous system involvement, interstitial lung disease, skin and orbital lesions, adrenal enlargement, retroperitoneal fibrosis and renal impairment as well fever, and weight loss. The disease is challenging to diagnose due to its rarity and mimicry of other infiltrative processes. Technetium-99 m bone scintigraphy showing pathological bone activity in the long bones is highly suggestive of ECD. However, not all patients have bone complaints. Till now, fluorine-18-fluorodeoxyglucose positron-emission tomography/computed tomography (18F-FDG PET/CT) was especially used after histological diagnosis to determine disease activity and extent, as well as the evaluation of treatment response. With this case, we suggest an additional role for 18F-FDG PET/CT earlier on in the diagnosis workup as follows: detecting a possible biopsy site to establish the diagnosis of ECD especially in a clinical context without bone pain.